Forschungsdaten in den Geisteswissenschaften: Bereits selbstverständlich oder doch noch etwas exotisch? - Blumesberger, Susanne (o-bib. Das offene Bibliotheksjournal / Herausgeber VDB, 2021)
This article deliberately focuses on data in the humanities that cannot be classified as digital humanities and thus does not per se consciously focus on the digital dimension of the discipline. At the latest when filling out the data management plans prescribed by the funding bodies, many scientists and scholars are confronted with the question of what actually constitutes the research data that they are supposed to make available securely and in the long term. Is it the text that is used or produced, or the images that the text refers to? Not dealing with data management while studying and writing the thesis not only leads to the loss of a lot of information that could be further used by other researchers, but also to legal uncertainties and, in the worst case, to legal problems. Finding the right path between withholding information for fear of legal consequences and handling data as openly as possible is a tightrope walk and requires precise instructions and a lot of background knowledge. This article will discuss how research data managers in libraries can best help humanities scholars to act “as open as possible, as closed as necessary”.
Keywords: Research Data; Humanities; Research Data Management; Requirements; Strategies